Roles of Institutional Quality on the Relationship between Tourism and Economic Development in Malaysia - Shan LEE, Hui; Yee LEE, Sin; Mun HAR, Wai (International Journal of Psychosocial Rehabilitation, 2020)
This research intends to examine the roles of institutional quality on tourism-led growth and growth led tourism hypothesis in Malaysia in both short run and long run analysis. This study uses yearly data from 1996 to 2015 to verify whether institutional quality significantly affects the relationship between tourism and economic growth in Malaysia. It provides a comprehensive dataset by investigating all the institutional quality dimensions including control of corruption, government effectiveness, regulatory quality, rule of law, voice and accountability, political stability and absence of violence in addition to the aggregate value and average value of these dimensions. The findings provide empirical supports that institutional quality such as control of corruption and government effectiveness do play important roles in the tourism and economic growth in Malaysia. In this essence, any policy planning that enhances the corruption and government effectiveness of Malaysia could promote the tourism development and economic growth in Malaysia.